Pengaruh Persepsi Muzaki terhadap Minat Membayar Zakat di BAZNAS - Fitri Rahmah; Ferdinan Ferdinan (AL-Muqayyad, 2022)
Muzaki's perception of zakat is important in influencing interest in paying zakat, because a broad perception of zakat will affect the interest of muzaki to pay zakat. The purpose of this study is to examine how much influence the perception of muzaki (variable X) has on interest in paying zakat (variable Y). In this study, the subject of this research is BAZNAS Tembilahan muzakki while the object of the research is the effect of muzakki's perception on interest in paying zakat. This type of research is quantitative research because the data obtained are a collection of numbers. By using a simple linear regression method. This research was conducted for 3 months. The results of the regression showed that the value of tcount > ttable was 9.666 > 2.068 with a significance of 0.000 <0.05. Thus, it can be concluded that there is a significant influence between the perception of muzakki on the interest in paying zakat at BAZNAS, Tembilahan District